Nationalized Companies: A Threat to American BusinessNationalized Companies: A Threat to American Business, by MonsenR. Joseph and WaltersKenneth D.. New York: Mc-Graw-Hill, 1983, 178 pp., $17.95 cloth. - McGowan, Robert P. (Academy of Management Review, 1985)
The article presents a review of the book ?Nationalized Companies: A Threat to American Business,? by R. Joseph Monsen and Kenneth D. Walters.